Strategi Meningkatkan Pemasaran Produk Perbankan Menggunakan Sistem Kluster Ekosistem - Putri Azahra, Nabila; Sasongko, Raden rudy Adhi; Furkan, M.; Sjah, Taslim (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2025)
This study analyzes strategies to enhance the marketing of banking products, particularly loans and savings, through an ecosystem cluster system. The case study of Bank BRI Praya is the central focus, revealing the implementation of cluster strategies by grouping SMEs, financial institutions, and local businesses into a single ecosystem to expand financial service access, foster partnerships, and strengthen capital flows. This approach aims to optimize local resource utilization, improve financial inclusion, and stimulate community business innovation. The study also identifies challenges in managing clusters, such as dependence on local economic health and the complexity of coordination among entities. The findings provide strategic insights into how ecosystem clusters can serve as effective tools to strengthen banking product marketing and promote sustainable regional economic growth